Cryptococcus: isolamento ambiental e caracterização bioquimica - Araújo Junior, Erivelto Corrêa de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Cryptococcosis is an opportunistic fungal infection caused by Cryptococcus yeasts, especially C. neoformans and Cryptococcus gattii, which may be associated with immunosuppression or not. The fungus is found in substrates of animal and vegetable origin, and infection occurs through inhalation and seedlings present in the environment. The present study aimed to investigate the existence of microfocus Cryptococcus sp. from the environmental samples Araçatuba city, São Paulo, featuring new niches, by decoupling the direct relationship between fungus and host. in order to minimize the risk of contamination of man and animals, understanding the ecoepidemiology of Cryptococcus. Samples 50 originated from hollow logs and trees (Cassia sp., Ficus sp. and Caesalpinea peltophorides) of ten point the urban perimeter points. The samples were immediately sent to the Laboratory of Bacteriology and Mycology, Faculty of Veterinary Medicine Araçatuba - Unesp where they were processed and plated on Petri dishes containing agar seed Niger and Sabouraud dextrose agar with chloramphenicol, incubated at 30ºC for a period not less than 5 days. Colonies yeast growth were analyzed considering the macro and micro morphological compatible gender Cryptococcus, and later peaked in Niger agar, grown in time and above temperature and subjected to biochemical tests: urease production, thermotolerance at 37°C and quimiotipagem in CGB agar (L- Canavanine, Glinica bromothymol blue). The results showed that 17 (34%) cultures were positive for Cryptococcus, and 9 (18% ) were Cryptococcus gattii and 8 (16%) for Cryptococcus neoformans. Other yeast correlated as Rhodotorula sp. and Candida sp. were isolated. For these reasons, we conclude that the infectious propagules of Cryptococcus are dispersed in nature constitute environmental microfocus, not necessarily being bound to a single host

Foram acompanhados 310 parturições de receptoras, com embriões fertilizados in vivo (FV) e in vitro (FIV) da raça Nelore, para determinar os índices de partos distócicos em receptoras meio sangue das raças Braford/Nelore, Hereford/Nelore, Simental/Nelore, Red Angus/Nelore, Nelore e anelorados, com idade entre três e seis anos, assim como avaliar o estado de saúde dos bezerros obtidos por intermédio de transferência de embriões, resultantes das técnicas de fertilização in vivo (FV) ou fertilização in vitro (FIV). Observou-se a ocorrência de 38 partos distócicos (38/310) e oito abortos (8/310), dos quais cinco fetos eram oriundos da técnica de fertilização in vivo (FV) e três da técnica de fertilização in vitro (FIV). A taxa de mortalidade em animais neonatos foi de 3,4% (10/290). Os bezerros nascidos de partos distócicos mais duradouros, entre quatro e seis horas, apresentaram os maiores valores médios de freqüência respiratória. A temperatura retal foi mais elevada em animais nascidos de partos laboriosos do que naqueles nascidos de partos normais.
Keywords: Microbiologia; Levedos; Arvores; Bioquímica; Imunossupressão; Cryptococcus